Art therapy as a primary and adjunct therapy in interventions for people living with serious illnesses - a review of the literature - Natalia Baran; Alicja Nowak; Aleksandra Nowak; Klaudia Bogusz; Łucja Cywka; Adriana Bielak; Weronika Szwed; Marcela Maksymowicz; Piotr Machowiec (Kazimierz Wielki University, 2023)
Introduction and purpose Art-therapy is a therapeutic method which uses art as a tool to achieve benefits in physical and mental health. This kind of psychotherapy uses artistic media as a basic form of communication. As an additional form of treatment, combined with medication, it helps not only to explore a patient's difficulties and problems but also to overcome them. Art-therapy is playing an increasing role in the context of health in individuals struggling with different diseases, especially with the mental ones. This is a growing field of research and the aim of this brief review is to provide an update on the positive effects of art-therapy and to list health problems in which it would be significant to use this kind of therapy. Materials and methods A search was conducted using PubMed and GoogleScholar data bases. Articles were searched in English using the following key words: "art therapy", "psychodrama", "dance movement therapy", "music therapy", "creative art therapy". Description of the state of knowledge Art-therapy has a wide range of benefits in chronically ill patients. Most common are the awareness of the emotions and behaviors and helping to deal with them, helping to deal with the process of treatment. The literature also draws attention to other results such as increasing self- esteem and improving the quality of life. Summary Art-therapy is associated with health benefits in people struggling with different health problems. Art-therapy has great potential to participate in future basic and adjunctive therapy but further research is needed in this area.